Life, Death, and Beyond: Multidimensional Analysis of ζωὴ αἰώνιος and Its Theological Implications in the Fourth Gospel - CHIANG, Yao-kuo Eric (Journal of Research for Christianity in China (JRCC), 2024)
This paper explores the concept of “eternal life” (ζωή αἰώνιος) in the Gospel of John and its theological implications. By reviewing four main interpretations of the meaning of “eternal life” in scholarly discourse – (1) everlasting life, (2) true, new, and spiritual life, (3) eschatological life of the future age, and (4) resurrected life – the paper highlights the clarity and prominence of the “resurrected life” perspective. Furthermore, it examines whether eternal life is a present reality or a future hope. The majority of scholars support the “present age view,” asserting that believers can obtain eternal life in the present while also acknowledging its future dimension, thus presenting a “two-stage view” of eternal life. Finally, the paper addresses the question of how to attain eternal life, emphasizing that in the Gospel of John, “faith” is the sole necessary and sufficient condition. However, this faith is not a superficial belief but a wholehearted commitment to and union with Christ. In summary, through a multidimensional analysis of eternal life, this paper elucidates the rich meaning and significant theological implications of the core message of the Gospel of John: “believing in Jesus to obtain eternal life.”